Neck kinesthesia as a significant contribution to the protection of postural stability in taekwondo fighters - Mesarič Ladislav; Romanov Romana; Majcen-Rošker Živa; Rošker Jernej (University Educons, Faculty of Sports and Tourism, Novi Sad, 2022)
Taekwondo fighters require sufficient postural stability to maintain tactical superiority over an opponent. Postural balance is controlled by somatosensory, visual and vestibular system. Cervical spine has neurophysiological connection to the visual and vestibular system as well as abundance of receptors within the connective tissues of the spine. Guard-specific posture in taekwondo requires constant head and neck rotations, therefore deficits in cervical spine could alter the balance. The aim of the study was to study connections between cervical spine kinesthesia and balance in taekwondo specific postural tasks. Sixteen healthy male taekwondo fighters (22 ±1,3 years of age) competing at the national level were enrolled in the study. Postural balance during a single leg stance while facing forward or with 90° of neck torsion using a force plate (Bilateral force plate, S2P, Ljubljana, Slovenia) was assessed. Kinesthetic awareness of cervical spine was measured using a Butterfly test with a NeckCare system (Butterfly Method, NeckCare ehf., Reykjavik, Iceland). Statistically significant correlations were observed for Undershoot standard deviation of the Butterfly test and Neck torsion balance test while standing on the non-dominant leg. These correlations were most prominent for the average amplitude of centre of pressure movement in the medial-lateral direction (r > 0.85) and anterior posterior direction (r > 0,80) Results of this study indicate that taekwondo fighters develop side specific adaptations in the balance control. Increased variability of cervical spine kinesthetic awareness is correlated to an increased average amplitude of medial-lateral body sway while standing on the kick preferred leg. This can lead to higher body oscillations during the fight, decreased stability, prolonged reaction time and quickness. Specific cervical spine training is recommended to improve fighting performance.